Baseline sensitivity and toxic action of flusilazole to Sclerotinia sclerotiorum. (December 2015) - Lu, Xiao-Ming; Zhu, Zu-Qing; Di, Ya-Li; Zhu, Fu-Xing
Abstract: The ascomycete fungus Sclerotinia sclerotiorum is a notorious plant pathogen with a broad host range and worldwide distribution. The demethylation inhibitor (DMI) fungicide flusilazole has not been registered for control of S. sclerotiorum in China. In this study, baseline sensitivity of S. sclerotiorum to flusilazole was established and toxic actions of flusilazole on S. sclerotiorum were assessed. The frequency distribution of flusilazole EC50 values of 150 isolates was unimodal, and the mean EC50 value was 0.1273 μg/ml with individual EC50 values ranging from 0.0227 to 0.3436 μg/ml. No significant ( P ≧ 0.152) positive or negative correlation was found between sensitivity to flusilazole and to tebuconazole or boscalid. Flusilazole sprayed at 90 μg/ml provided a preventive efficacy of 85.2% and a curative efficacy of 58.9% against S. sclerotiorum on potted oilseed rape plants. After growing on potato dextrose agar (PDA) amended with flusilazole at 0.05, 0.1 and 0.2 μg/ml for 21 d, the number and weight of sclerotia per plate were significantly reduced ( P < 0.05) compared to the untreated control. Mycelial cell membrane permeability was significantly lower ( P < 0.05) for S. sclerotiorum grown on PDA amended with flusilazole at 0.03, 0.06 or 0.12 μg/ml than that of the untreated control. The reduced cell membrane permeability might be due to the thickening of mycelial cell walls after growing on flusilazole-amended PDA, as indicated by transmission electron microscopy (TEM) observations. Highlights: Baseline sensitivity of Sclerotinia sclerotiorum to flusilazole was established. Flusilazole has high preventive efficacy against S. sclerotiorum. Flusilazole reduced Sclerotia production and mycelial cell membrane permeability. Hyphal cell wall became thicker after treated with flusilazole.